2020
DOI: 10.1001/jamaoncol.2020.2485
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of a Deep Learning Algorithm for Gleason Grading of Prostate Cancer From Biopsy Specimens

Abstract: IMPORTANCE For prostate cancer, Gleason grading of the biopsy specimen plays a pivotal role in determining case management. However, Gleason grading is associated with substantial interobserver variability, resulting in a need for decision support tools to improve the reproducibility of Gleason grading in routine clinical practice. OBJECTIVE To evaluate the ability of a deep learning system (DLS) to grade diagnostic prostate biopsy specimens. DESIGN, SETTING, AND PARTICIPANTS The DLS was evaluated using 752 de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
116
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 148 publications
(132 citation statements)
references
References 37 publications
1
116
0
2
Order By: Relevance
“…In this study, we present an algorithm for automated Gleason grading that could be used as a screening tool, improving the accuracy of PCa diagnosis and reducing pathologists' workload. Several studies on this subject have been published in recent years [10,12,[15][16][17]20], indicating that there is a strong interest and need for the development of such tools. The present study is the first to evaluate an AI algorithm on a cohort scanned on two different slide scanners, comparing their results pixel by pixel.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, we present an algorithm for automated Gleason grading that could be used as a screening tool, improving the accuracy of PCa diagnosis and reducing pathologists' workload. Several studies on this subject have been published in recent years [10,12,[15][16][17]20], indicating that there is a strong interest and need for the development of such tools. The present study is the first to evaluate an AI algorithm on a cohort scanned on two different slide scanners, comparing their results pixel by pixel.…”
Section: Discussionmentioning
confidence: 99%
“…We demonstrate its robustness by obtaining very similar results on scans from two different scanners. Nagpal et al [17] show encouraging results but lack testing on different scanners. Ström et al [15] tested their algorithm on an external set scanned on a different scanner, but the slides in this set differed from those used in the testing cohort.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is also confirmed by the increasing number of papers on the topic. Nagpal et al [ 34 ] developed a DL algorithm using as reference a group of expert uropathologists, and reported that their model performed significantly better than general pathologists on tumor grading in prostatic biopsy (71.7% versus 58.0%; p < 0.001). Interestingly enough, the AI algorithm achieved the same results of general pathologists in the recognizing the presence of tumor (94.3% for the AI and 94.7% for general pathologists).…”
Section: Tissue Biomarkers and Artificial Intelligencementioning
confidence: 99%
“…The use of proportionate grading is becoming easier with better access to image repositories and related data, as well as increased computational ability for complex artificial intelligence (AI) models. Research has shown that the accuracy and consistency of AI algorithms, when it comes to grading, are similar or even better than that of the general pathologists [ 23 , 24 , 25 ]. AI could make cancer detection and grade assessment more efficient and less prone to human error in the future.…”
Section: Quantitative Gleason and Artificial Intelligencementioning
confidence: 99%